Loranthus acaciae (Plicosepalus acacia): The Proving - Onne, Elia; Yakir, Michal (Homœopathic Links, 2016)
The Loranthus proving was shrouded in an atmosphere of animosity and suspicion. The thread of scarlet seemed to be: taking or claiming rights of things, which are not yours or feeling like a victim of such circumstances, feeling that one is overpowered by malicious force and being leeched upon. There is hatred for those you depend on or for those that are dependent (or use) you. This was responded to with resistance to any authority, by belligerence, and by a dictatorial, bitter, aggressive and impatient attitude. It is an uncompromising rivalry that is fuelled by an undercurrent conviction that it's ‘either me or you’.
Keywords: Loranthus acaciae; Parasites; Column five; Hatred; Power games; Being taken over; Flu-like; Humility; Love; Generosity